2013
DOI: 10.1128/aac.00505-13
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the Role of Pseudomonas aeruginosa Penicillin-Binding Protein 5 in β-Lactam Resistance

Abstract: b Penicillin-binding protein 5 (PBP5) is one of the most abundant PBPs in Pseudomonas aeruginosa. Although its main function is that of a cell wall DD-carboxypeptidase, it possesses sufficient ␤-lactamase activity to contribute to the ability of P. aeruginosa to resist the antibiotic activity of the ␤-lactams. The study of these dual activities is important for understanding the mechanisms of antibiotic resistance by P. aeruginosa, an important human pathogen, and to the understanding of the evolution of ␤-lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 63 publications
(72 reference statements)
1
43
0
Order By: Relevance
“…The most highly expressed PBP in P. aeruginosa membranes has been documented to be PBP5 (40), consistent with the results of our work. It was recently shown that PBP5 is a DD-carboxypeptidase that preferentially degrades low-molecularweight substrates (28). In this work, we confirm that PBP5 is the major DD-carboxypeptidase in P. aeruginosa, as evidenced by the fact that of the three LMM PBP single mutants, only dacC mutation led to significantly increased pentapeptide levels.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The most highly expressed PBP in P. aeruginosa membranes has been documented to be PBP5 (40), consistent with the results of our work. It was recently shown that PBP5 is a DD-carboxypeptidase that preferentially degrades low-molecularweight substrates (28). In this work, we confirm that PBP5 is the major DD-carboxypeptidase in P. aeruginosa, as evidenced by the fact that of the three LMM PBP single mutants, only dacC mutation led to significantly increased pentapeptide levels.…”
Section: Discussionsupporting
confidence: 76%
“…Purified E. coli PBP5 failed to show significant ␤-lactamase activity, and therefore it was concluded that the role of this PBP in intrinsic ␤-resistance might be a consequence of ␤-lactam trapping. However, interestingly, the recently crystalized P. aeruginosa PBP5 does show certain broad-spectrum (including to penicillins, cephalosporins, and carbapenems) ␤-lactamase activity (28). Therefore, the observed effect of PBP5 in P. aeruginosa intrinsic resistance is expected to result from both trapping and hydrolysis of ␤-lactams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of dacC results in increased pentapeptides establishing its role as the primary carboxypeptidase in P. aeruginosa [123,125,126]. P. aeruginosa encodes a homologue of BolA (PA0857), which shows a 46 % identity to their E. coli counterpart.…”
Section: Low Molecular Mass Penicillin-binding Proteins (Lmm Pbps)mentioning
confidence: 99%
“…LMM PBPs in P. aeruginosa include PBP4/DacB (PA3047), PBP5/DacC (PA3999) and PBP7/PbpG (PA0869) [66,[122][123][124][125]. Loss of dacC results in increased pentapeptides establishing its role as the primary carboxypeptidase in P. aeruginosa [123,125,126].…”
Section: Low Molecular Mass Penicillin-binding Proteins (Lmm Pbps)mentioning
confidence: 99%